2015
DOI: 10.5606/ehc.2015.36
|View full text |Cite
|
Sign up to set email alerts
|

One-stage surgical treatment of neglected simultaneous bilateral locked posterior dislocation of shoulder: a case report and literature review

Abstract: Bilateral posterior or anterior dislocations of the shoulder joint are rare. [1,2] Most posterior shoulder dislocations have been attributed to high energy trauma, seizures or electroconvulsive therapy. [3] Misdiagnosis of this injury may occur in 50% to 79% of patients, most commonly due to lack of clear clinical signs and accurate imaging study findings. [4,5] Computed tomography can quantify the involvement of the articular surface of the humeral head and identify fractures of the tuberosity, surgical neck,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Although the literature contains many case reports dealing with the neglected posterior shoulder dislocation, 9 , 11 , 14 , 15 , 16 only a limited number of case series are available that report on the transfer of the lesser tuberosity. 1 , 12 , 17 In the study by Hawkins et al, satisfactory outcomes were reported in 4 patients with a mean follow-up of 5.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature contains many case reports dealing with the neglected posterior shoulder dislocation, 9 , 11 , 14 , 15 , 16 only a limited number of case series are available that report on the transfer of the lesser tuberosity. 1 , 12 , 17 In the study by Hawkins et al, satisfactory outcomes were reported in 4 patients with a mean follow-up of 5.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…[15] For these medium sized defects, other surgical options are derotation osteotomy of the humerus and reconstruction of the head with allograft or autograft. [2,16,17] Hemiarthroplasty may be performed for large defects involving more than 50% of the head, while total shoulder arthroplasty may be performed for large defects with glenoid destruction. [18] Subscapularis transfer, tuberculum minus transfer and derotation osteotomy are techniques which deteriorate normal anatomy and biomechanics of the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs secondary to epileptic seizure and most of them are posterior. [1,2] Posterior shoulder dislocations are frequently associated with an anterior impression fracture of the humeral head. The size of this impression defect, the reverse Hill-Sachs or the McLaughlin lesion designates the treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations